Supplementary dataset to "Honeydew production by the Giant Willow Aphid (Tuberolachnus salignus, Hemiptera: Aphididae) and its effect on foraging yellowjackets (Hymenoptera: Vespidae)" - Martinez, Andres; Buteler, Micaela; Villacide, Jose Maria; Serra, María Noel; Masciocchi, Maite (2022)
This study was financed by project BID PICT 2018-0657 provided by the “Agencia Nacional de Promoción Científica y Tecnológica” (Argentina) to AM, project PUE 0069 2018-IFAB provided by the “Consejo Nacional de Investigaciones Científicas y Técnicas” and project 2019-PE-E1-I017-001.P14 and project 2019-PD-E4-I079-001 provided by the “Instituto Nacional de Tecnología Agropecuaria”